1991
DOI: 10.1136/gut.32.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption in patients with colorectal adenomatous polyps.

Abstract: The risk ofdeveloping colorectal adenomatous polyps is probably increased by a variety of dietary and environmental factors. We found an association with current alcohol and cigarette consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(22 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…The prospective studies of health professionals also suggested an independent risk associated with high alcohol consumption, 5,15 an association that has been demonstrated for adenomatous polyps in some recent case-control studies, [31][32][33][34] but not in others. 26,[35][36][37][38][39][40] Three case-control studies found an association between high alcohol consumption and adenomatous polyps among men, but not among women.…”
Section: Discussionmentioning
confidence: 99%
“…The prospective studies of health professionals also suggested an independent risk associated with high alcohol consumption, 5,15 an association that has been demonstrated for adenomatous polyps in some recent case-control studies, [31][32][33][34] but not in others. 26,[35][36][37][38][39][40] Three case-control studies found an association between high alcohol consumption and adenomatous polyps among men, but not among women.…”
Section: Discussionmentioning
confidence: 99%
“…Chan et al (32) We found ten studies (1,5,7,10,12,13,16,29,33,34) regarding the association between ethanol consumption and colon polyps where all polyps were diagnosed by full colonoscopy. Three (1,13,16) of the ten studies also investigated the association between ethanol and HP.…”
Section: T a B L E 3 Ad J U S T E D Od D S Ra T I O S F O R Co L O mentioning
confidence: 99%
“…Regarding the association between colorectal adenoma and obesity, we have found four studies (21)(22)(23)(24) (25) reported that high BMI is not associated with colorectal adenoma but visceral o p l a s i a a n d Hy p e r p l a s t i c P o l y (1,7,9,11,29) from the meta-analysis.…”
Section: Our Study Showed That Aging Was a Significant Risk Factor Fomentioning
confidence: 99%
See 2 more Smart Citations